Effect of Preceding Winter Crops and Residue Management on Growth Performance, Weed, Nutrient Uptake and Economics of Clusterbean (Cyamopsis Tetragonoloba L. Taub.] Under Zero-Till Semi-Arid Condition - Amgain, L. (Journal of the Institute of Agriculture and Animal Science, 2018)
Field experiments under zero-till rainfed ecosystem were conducted during 2010-11 and 2011-12 at Indian Agricultural Research Institutive New Delhi for identifying the agronomic performance, weed dynamics, nutrient uptake and profitability of clusterbean based cropping systems (clusterbean-wheat, clusterbean-mustard and clusterbean-chickpea) as influenced by three residue management practices (no residue, crop residues and Leucaena twigs) applied to both summer and winter seasonal crops. Randomized Complete Block Design with four replications were used to conduct the trials. Significantly higher green-pod yield of clusterbean (10.08 t ha-1 and 6.70 t ha-1) was recorded with the application of Leucaena twigs, followed by crop residue mulching and the least with no-residue application in 2010 and 2011, respectively. Wheat and chickpea as preceding crops produced significantly higher clusterbean green-pod yield (6.54 t ha-1 and 6.43 t ha-1) than mustard (5.18 t ha-1). The yield attributes viz. pod-clusters and weight of pods per plant showed significant variation. Significantly higher dry matter yield (299.9 g m-2) of Cyperus iria was recorded with mustard residues followed by chickpea (253.1 g m-2) and wheat (194.0 g m-2) residues. The nutrient uptake showed the same trend as that of dry pod and stalks yields and resulted significant influence due to residue management and preceding crops. Economic analysis exhibited the highest returns and net returns per Rupee invested under wheat with Leucaena twigs followed by chickpea with Leucaena twigs. Clusterbean after wheat and chickpea with Leucaena twigs was high yielding and profitable for rainfed areas under zero-till semi-arid condition.